Bilateral Gastrocnemius Muscle Rupture in a Bovine - Mori, Ana Paula; Schwertz, Claiton Ismael; Henker, Luan Cleber; Stedille, Fernanda Augustini; Christ, Ricardo; Lorenzett, Marina Paula; Broll, Fabrisio; Mendes, Ricardo Evandro (Acta Scientiae Veterinariae, 2017)
Background: Locomotor system diseases are quite common in the field practice in dairy cattle and represent an important cause of economics losses. The rupture of the gastrocnemius muscle has been reported in humans, cattle, horses, camels and llamas. It can be complete or partial. The rupture of muscle as well as sacral fractures are infrequent, and consequently not commonly reported in veterinary medicine. The aim of this work was to report a case of bilateral gastrocnemius rupture in a dairy cow related to a sacral (S2) fracture. Case: A 3-year-old Holstein cow with lameness and urinary incontinence was presented for clinical examination. After three days, clinical signs progressed to sternal recumbency and difficulty to keep normal posture. While standing, the cow’s tarsal joint showed a 90o degree angle with tibia, in a manner that the metatarsal bones were completely leant on the ground. Also, a marked enlargement in both gastrocnemius area were observed. The animal was in good body condition and alert, although unable to maintain both hind limbs extended straight, and was not able to raise the tarsal joint off the ground. Physiological parameters presented normal values. Due to the poor prognosis, euthanasia and necropsy were conducted. At necropsy, it was observed that in both hind limbs the gastrocnemius muscle was ruptured, presenting severe diffuse dark red color, severe enlargement, and moderate diffuse edema and emphysema. The rupture was complete and observed at both muscular insertions in the calcaneus bone. Besides the muscular alterations, the animal had a 2 centimeters fracture on the second sacral vertebra, associated with focally extensive hemorrhage in the spinal canal and meninges. Histologically the main findings were degeneration and severe diffuse necrosis of muscle fibers associated with severe hemorrhage, and mild infiltrate of neutrophils. Discussion: Fractures in cattle may occur due to multiples causes, however farm management and facilities play an important role in the incidence of these disorders. Slippery floors along with groups composed of animals of different sizes and ages are a major cause of injury in this species. The consequence of a vertebral fracture vary greatly according to the location and extent of the injury, the degree of spinal cord compression and which spinal anatomical structures are involved. Besides the direct damage caused by the fractures in the bone’s stability, changes can also occur in related structures, such as muscles and tendons, which are extremely important for the animal to maintain its normal stance and move adequately. One example is the trauma of gastrocnemius muscle that is found sporadically due to struggling. In this case it is conjectured that the pain and the spinal cord compression at the fracture’s location, lead to difficulty for the animal to rise, culminating with the ruptured muscles by overexertion. The characteristic position adopted by the animal was useful to establish the diagnosis, although necropsy was necessary to confirm it. Once the occurrence of this condition is infrequent, this report becomes important to aid veterinarians in order to differentiate it from other diseases of the musculoskeletal and nervous systems, including toxic conditions as Senna sp. and ionophore poisoning, besides nutritional myopathies such as vitamin E and selenium deficiency. Coxofemoral luxation and infectious diseases such as rabies and botulism should also be considered.